"They've walked the walk": A systematic review of quantitative and qualitative evidence for parent-to-parent support for parents of babies in neonatal care. Issue 4 (August 2019) - Hunt, Harriet; Abbott, Rebecca; Boddy, Kate; Whear, Rebecca; Wakely, Leanna; Bethel, Alison; Morris, Christopher; Prosser, Susan; Collinson, Andrew; Kurinczuk, Jennifer; Thompson-Coon, Jo
Abstract: The aim of this systematic review was to explore the effects and experiences of parent-to-parent support in neonatal intensive care from the perspectives of those giving, receiving, or implementing support. Electronic database searches (14 databases; February 2018) were supplemented with forward and backward citation chasing. Study selection, data extraction and quality appraisal were performed independently by two reviewers. Fourteen studies (6 quantitative and 8 qualitative) met our inclusion criteria. Four major themes were identified in the qualitative literature: 'trust', 'hope', 'information', and 'connecting'. Quantitative studies showed parent-to-parent support increased perceptions of support, reduced maternal stress, and increased mothers' confidence in the ability to care for their baby. Whilst the rich qualitative evidence suggested mostly positive experiences of parent-to-parent support from all perspectives, robust trial evidence was lacking. Furthermore, differences in models for implementing parent-to-parent support provided limited opportunities to develop recommendations to guide best practice. The protocol for this study was registered on PROSPERO, registration number CRD42018090569.